Technology integration in foreign language teacher training programs: Exploring cutting-edge tools and applications for professional development - Koka, Nisar Ahmad; Ahmad, Javed; Jan, Nusrat; Khasawneh, Mohamad Ahmad Saleem (Research Journal in Advanced Humanities, 2025)
The incorporation of technology into the training of foreign language teachers has garnered considerable interest among educators, who have increasingly acknowledged the inherent possibilities of innovative tools and applications in augmenting their professional growth. Notwithstanding, these tools allow educators to remain abreast of the most current pedagogical methodologies, augment their instructional expertise, and proficiently cater to the varied requirements of students. This study investigates the incorporation of these tools within the instructional program of educators specializing in foreign languages; with the ultimate aim of unveiling the views of relevant stakeholders on how these tools aid in strengthening their professional growth. The study involved the participation of 107 individuals, comprising both foreign language university lecturers and teacher trainers. Furthermore, a quantitative method of analysis was adopted in analyzing the research data that was collated through the use of an online questionnaire.  Several significant findings were made from the research data which were presented and analyzed. The research findings revealed that technology integration seamlessly paves the way for the professional development of foreign language educators. Also, a comprehensive training program, provision of ongoing professional development opportunities, peer collaboration, and establishment of feedback and evaluation mechanisms can aid in countering major limitations of the implementation of technology integration.